The prevalence of complications associated with lumbar and thoracic spinal deformity surgery in the elderly population: a meta-analysis - Smith, Colleen; Lamba, Nayan; Ou, Zhonghui; Vo, Quynh-Anh; Araujo-Lama, Lita; Lim, Sanghee; Joshi, Dhaivat; Doucette, Joanne; Papatheodorou, Stefania; Tafel, Ian; Aglio, Linda S.; Smith, Timothy R.; et al. (Journal of Spine Surgery; Vol 5, No 2 (June 29, 2019): Journal of Spine Surgery, 2019)
Background: The prevalence of spinal deformities increases with age, affecting between 30% and 68% of the elderly population (ages ≥65). The reported prevalence of complications associated with surgery for spinal deformities in this population ranges between 37% and 71%. Given the wide range of reported complication rates, the decision to perform surgery remains controversial. Methods: A comprehensive search was conducted using PubMed, Embase, and Cochrane to identify studies reporting complications for spinal deformity surgery in the elderly population. Pooled prevalence estimates for individual complication types were calculated using the random-effects model. Results: Of 5,586 articles, 14 met inclusion criteria. Fourteen complication types were reported, with at least 2 studies for each complication with the following pooled prevalence: reoperation (prevalence 19%; 95% CI, 9–36%; 107 patients); hardware failure (11%; 95% CI, 5–25%; 52 patients); infection (7%; 95% CI, 4–12%; 262 patients); pseudarthrosis (6%; 95% CI, 3–12%; 149 patients); radiculopathy (6%; 95% CI, 1–33%; 116 patients); cardiovascular event (5%; 95% CI, 1–32%; 121 patients); neurological deficit (5%; 95% CI, 2–15%; 248 patients); deep vein thrombosis (3%; 95% CI, 1–7%; 230 patients); pulmonary embolism (3%; 95% CI, 1–7%; 210 patients); pneumonia (3%; 95% CI, 1–11%; 210 patients); cerebrovascular or stroke event (2%; 95% CI, 0–9%; 85 patients); death (2%; 95% CI, 1–9%; 113 patients); myocardial infarction (2%; 95% CI, 1–6%; 210 patients); and postoperative hemorrhage (1%; 95% CI, 0–10%; 85 patients). Conclusions: Most complication types following spinal deformity surgery in the elderly had prevalence point estimates of